2006
DOI: 10.1158/1078-0432.ccr-05-0848
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Carbonic Anhydrase IX in Astrocytic Tumors Predicts Poor Prognosis

Abstract: Purpose: Carbonic anhydrase IX (CA IX) is a hypoxia-inducible enzyme, which is associated with neoplastic growth. Ectopic CA IX expression has been observed in several tumors, whose normal counterparts do not express this enzyme. Normal human brain tissue shows only slight or no expression of CA IX. Experimental Design: We describe CA IX expression in human diffusely infiltrating astrocytomas. The association of CA IX is evaluated with clinicopathologic and molecular factors including cell proliferation and ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
101
1
4

Year Published

2008
2008
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 25 publications
8
101
1
4
Order By: Relevance
“…In terms of IHC score, CA9 expression was significantly associated with tumour staging and poor prognosis. In other solid tumours, CA9 protein has been reported to be an independent factor related to poor prognosis (Chia et al, 2001;Loncaster et al, 2001;Brennan et al, 2006;Haapasalo et al, 2006;Lee et al, 2007). Driessen et al reported that CA9 expression was an independent prognostic marker in oesophageal cancers, especially adenocarcinomas and gastric cancer (Driessen et al, 2006), whereas in another study of oesophageal tumours, the degree of CA9 staining did not correlate CA9 expression in oesophageal squamous cell carcinoma N Tanaka et al with any of the pathological features examined (Turner et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of IHC score, CA9 expression was significantly associated with tumour staging and poor prognosis. In other solid tumours, CA9 protein has been reported to be an independent factor related to poor prognosis (Chia et al, 2001;Loncaster et al, 2001;Brennan et al, 2006;Haapasalo et al, 2006;Lee et al, 2007). Driessen et al reported that CA9 expression was an independent prognostic marker in oesophageal cancers, especially adenocarcinomas and gastric cancer (Driessen et al, 2006), whereas in another study of oesophageal tumours, the degree of CA9 staining did not correlate CA9 expression in oesophageal squamous cell carcinoma N Tanaka et al with any of the pathological features examined (Turner et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…CA9 expression has been associated with poor prognosis in patients with lung, breast, cervical, brain, and renal cancer (Chia et al, 2001;Giatromanolaki et al, 2001;Loncaster et al, 2001;Bui et al, 2003;Brennan et al, 2006;Haapasalo et al, 2006) and with resistance to chemotherapy in head and neck cancers . It has been reported that CA9 expression is an independent prognostic marker in oesophageal and gastric adenocarcinomas (Driessen et al, 2006), but the relationship between prognosis and CA9 expression in oesophageal squamous cell carcinoma (ESCC) remains controversial.…”
mentioning
confidence: 99%
“…The same authors also showed that acidification of the tumour microenvironment is attributed to the accumulation not only of lactic acid, but also of CO 2 , suggesting a possible contribution of carbonic anhydrase 9 (CA9). CA9 is induced by hypoxia and its expression is correlated with malignancy in gliomas [92][93][94][95]. There is evidence that CA9 is involved in the regulation of both extracellular and intracellular pH [96,97] suggesting that CA9 activity is needed for the survival of hypoxic cells and that its inhibition may represent a promising therapeutic approach.…”
Section: Hif-1 Regulated Metabolismmentioning
confidence: 99%
“…CA isozymes II, IX and XII have been extensively studied for their important role as promising biomarkers in different tumors, for example astrocytic tumors [5][6][7]. Other important research targets focused on CAs have included hypoxia-regulation of certain CA isozymes and their potential use as targets of cancer therapy [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%